Multilevel Transmission of Cultural Attitudes and Entrepreneurial Intention: Evidence from High-School Students - Annie Tubadji; Enrico Santarelli; Roberto Patuelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Intention toward any occupational choice can be widely categorized as a rational choice process combined with a subjective attitude function. There is extensive literature dealing with the formation of intention toward entrepreneurship in adolescents, in particular as a result of either parental (vertical) transmission of social capital or network effects from peers or neighbours (the latter two being two different levels of horizontal transmission varying in proximity in terms of bonding and bridging). We contribute to this literature by considering the joint effect of all these three levels simultaneously, in order to avoid an underspecification of the model due to omission of important cultural factors. We hypothesize that such three levels identify a mechanism where the individual perception of their importance interacts with their objective characteristics. With data for second-year high-school students, and employing empirical triangulation through Logit and 3SLS methods, we find evidence for a strong parental effect and of secondary peer effects on student intention. We also detect clear endogenous effects from the neighbourhood and the overall cultural context. Moreover, entrepreneurship is confirmed to be perceived, even by students, as a buffer for unemployment and social mobility.
Keywords: R32; R38; Z10; J60; 330